Incorporation of HA into porous titanium to form Ti-HA biocomposite foams. (August 2019) - Shbeh, Mohammed; Wally, Zena J.; Elbadawi, Mohammed; Mosalagae, Mosalagae; Al-Alak, Hassan; Reilly, Gwendolen C.; Goodall, Russell
Abstract: Ti foams are advanced materials with great potential for biomedical applications as they can promote bone ingrowth, cell migration and attachment through providing interconnected porous channels that allow the penetration of the bone-forming cells and provide them with anchorage sites. However, Ti is a bio-inert material and thus only mechanical integration is achieved between the porous implant and the surrounding tissue, not the chemical integration which would be desirable. In this work particles of a biologically active material (Hydroxyapatite, HA) are blended with titanium powder, and used to produce Ti foams through the use of Metal Injection Moulding (MIM) in combination with a space holder. This produces titanium foams with incorporated HA, potentially inducing more favourable bone response to an implant from the surrounding tissue and improving the osseointegration of the Ti foams. To be able to do this, samples need to show sufficient mechanical and biocompatibility properties, and the foams produced were assessed for their mechanical behaviour and in vitro biological response. It was found that the incorporation of high levels of HA into the Ti foams induces brittleness in the structure and reduces the load bearing ability of the titanium foams as the chemical interaction between Ti and HA results in weak ceramic phases. However, adding small amounts of HA (about 2 vol%) was found to increase the yield strength of the Ti foams by 61% from 31.6 MPa to 50.9 MPa. Biological tests were also carried out in order to investigate the suitability of the foams for biomedical applications. It was found that Ti foams both with and without HA (at the 2 vol% addition level) support calcium and collagen production and have a good level of biocompatibility, with no significant difference observed between samples with and without the HA addition. Graphical abstract: Image 1 Highlights: The addition of >2 vol% HA into Ti foams induces brittleness in the structure. Adding 2 vol% HA increases the yield strength of Ti foams by 61% from 31.6 to 50.9 MPa. Ti foams both with 2 vol% HA and without HA support calcium and collagen production.